2003
DOI: 10.1177/02698811030173010
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Central Noradrenaline: Effects on Mood, Cognitive Performance, Eye Movements and Cardiovascular Function

Abstract: There have been numerous studies on the effects of caffeine on behaviour and cardiovascular function. It is now important to clarify the mechanisms that underlie such effects, and the main objective of the present study was to investigate whether changes in central noradrenaline underlie some of the behavioural and cardiovascular effects of caffeine. This was examined using a clonidine challenge paradigm. Twenty-four healthy volunteers were assigned to one of four conditions: (i) clonidine/caffeine; (ii) cloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
64
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 58 publications
7
64
1
Order By: Relevance
“…The reaction time results here are also comparable with studies of alert people showing improvements after caffeine administration (Lorist et al 1994;Smith et al 2003;and summarized in Vanderveen et al 2001).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The reaction time results here are also comparable with studies of alert people showing improvements after caffeine administration (Lorist et al 1994;Smith et al 2003;and summarized in Vanderveen et al 2001).…”
Section: Discussionsupporting
confidence: 89%
“…The only other study that could be found regarding caffeine and ocular variables was one where clonidine was administered in order to lower arousal levels (Smith et al 2003). Interestingly, the caffeine was able to counteract the decreases shown in saccade velocity caused by clonidine (Smith et al 2003). It is possible that in these previous studies, the ocular variables measured were not sensitive enough to changes in alertness generally in order to demonstrate changes in alertness due to caffeine consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of nicotine a complex interaction with attention and memory occurs (Warburton 1992;Newhouse et al 2004;Rusted et al 2005), while caffeine reduces tiredness (Lieberman 2001;Smith et al 2003;Tieges et al 2004). In more recent years, a wide array of drugs have been developed that affect cognition (Farah et al 2004).…”
Section: Drugsmentioning
confidence: 99%
“…The stimulant effects of caffeine are not due to direct actions on the central nervous system, but to indirect stimulation by inducing blockade of another neuromodulator, adenosine, which usually exerts a calming effect on brain and spinal cord neurons 22 . Caffeine increases the amount of adrenaline and noradrenaline secreted by the adrenal medulla 23 and increases central noradrenaline synthesis and turnover in the cerebral cortex, consequently exerting a stimulatory effect and boosting wakefulness 24 . In a U.S. study, 41% of school-aged children were found to consume at least one caffeinated beverage per day.…”
Section: Discussionmentioning
confidence: 99%